A Review Of The Key Provisions Of The Petroleum Industry Bill And The Implications On Deregulation - Babayomi, Olutumbi Abiodun (Journal of Sustainable Development Law and Policy, 2025)
For many years, Nigeria has been classified globally as a fitting illustration of a nation suffering from the resource curse problem. This is because after decades of oil production, many parts of Nigeria have little or nothing to show in terms of social, environmental and economic development. In a bid to break loose from the resource curse classification, attempts have been made to upgrade the Nigerian oil and gas legal framework in order to boost real growth and development. The proposed legislation, the Petroleum Industry Bill (PIB), is currently under legislative consideration and represents the most comprehensive review of the legal framework for the oil and gas sector in Nigeria since the industry began commercial operations in the 1960s. It could signal the dawn of a new era; an era in which restructuring and transformation could address many of the issues that have dominated the oil and gas industry in Sub-saharan Africa’s second-biggest economy. However, despite its radical promises, the PIB has constantly met a brick wall at the National Assembly. It then comes to question the reasons for this delay. If the proposed bill will do more harm than good to the country, why then has it been ingloriously delayed? This paper x-rays and reviews the potential contributions and key provisions of the PIB amongst other things for the stability and growth of the Nigerian oil and gas industry. It also comments on why the current brick wall facing the PIB must be rapidly addressed.